2003
DOI: 10.1152/jn.00554.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Release of Adenosine Contributes to Short-Term Depression at CA3-CA1 Synapses in Rat Hippocampus

Abstract: Brager, Darrin H. and Scott M. Thompson. Activity-dependent release of adenosine contributes to short-term depression at CA3-CA1 synapses in rat hippocampus. J Neurophysiol 89: 22-26, 2003. 10.1152/jn.00554.2002. High-frequency stimulation results in a transient, presynaptically mediated decrease in synaptic efficacy called short-term depression (STD). Stimulation of Schaffer-collateral axons at 10 Hz for 5 s resulted in approximately 75% depression of excitatory postsynaptic current (EPSC) slope recorded fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
17
1
Order By: Relevance
“…Previous studies have shown that activity-dependent increases in adenosine and activation of presynaptic A1 receptors can inhibit transmitter release at Schaffer collateral fiber inputs onto CA1 pyramidal cells, although only during much higher frequencies of synaptic stimulation than those used in our experiments (Brager and Thompson 2003;Manzoni et al 1994;Mitchell et al 1993). We find, however, that monosynaptic EPSPs elicited by Schaffer collateral fiber stimulation are not inhibited by short trains of 1-Hz stimulation.…”
Section: Activity-dependent Modulation Of Recurrent Synaptic Connecticontrasting
confidence: 59%
“…Previous studies have shown that activity-dependent increases in adenosine and activation of presynaptic A1 receptors can inhibit transmitter release at Schaffer collateral fiber inputs onto CA1 pyramidal cells, although only during much higher frequencies of synaptic stimulation than those used in our experiments (Brager and Thompson 2003;Manzoni et al 1994;Mitchell et al 1993). We find, however, that monosynaptic EPSPs elicited by Schaffer collateral fiber stimulation are not inhibited by short trains of 1-Hz stimulation.…”
Section: Activity-dependent Modulation Of Recurrent Synaptic Connecticontrasting
confidence: 59%
“…1) indicates that the local synthesis/replenishment of ATP can occur at sites of high activity and independently of mitochondria, at least in the short-term, and may permit the "on-demand" nature of synaptic adenosine release which dampens presynaptic excitation [85][86][87][88]. This local, extra-mitochondrial, generation of ATP has an important additional advantage in the context of brain injury due to the mitochondrial dysfunction that can follow.…”
Section: The Purine Salvage Pathway As the Vehicle For Atp Replenishmentmentioning
confidence: 99%
“…The antagonist eliminated age differences in theta-burst facilitation, suggesting that adenosine build-up during the train either (1) disrupts the facilitation process itself or (2) simply depresses release and thereby offsets the effects of facilitation. It is likely that TBS elevates extracellular adenosine levels given evidence that afferent activity releases adenosine in hippocampus (Schubert et al, 1976;Dunwiddie and Masino, 2001) to a degree sufficient to cause homosynaptic and heterosynaptic depression (Mitchell et al, 1993;Brager and Thompson, 2003). These physiological effects appear within 50 ms and are generated by short afferent bursts (Mitchell et al, 1993), conditions that fall well within the parameters of TBS.…”
Section: Discussionmentioning
confidence: 97%